Mechanistic insights into the early life stage microbiota of silver pompano (Trachinotus blochii) - Sumithra, T. G.; Sharma, S. R. Krupesha; Suresh, Gayathri; Gop, Ambarish P.; Surya, S.; Gomathi, P.; Anil, M. K.; Sajina, K. A.; Reshma, K. J.; Ebeneezar, Sanal; Narasimapallavan, Iyyapparaja; Gopalakrishnan, A. (Frontiers in Microbiology, 2024)
Deep investigations of host-associated microbiota can illuminate microbe-based solutions to improve production in an unprecedented manner. The poor larval survival represents the critical bottleneck in sustainable marine aquaculture practices. However, little is known about the microbiota profiles and their governing eco-evolutionary processes of the early life stages of marine teleost, impeding the development of suitable beneficial microbial management strategies. The study provides first-hand mechanistic insights into microbiota and its governing eco-evolutionary processes in early life stages of a tropical marine teleost model, Trachinotus blochii. A less diverse but abundant core microbial community (~58% and 54% in the whole microbiota and gut microbiota, respectively) was observed throughout the early life stages, supporting ‘core microbiota’ hypothesis. Surprisingly, there were two well-differentiated clusters in the whole microbiota profiles, ≤10 DPH (days post-hatching) and >10 DPH samples. The levels of microbial taxonomic signatures of stress indicated increased stress in the early stages, a possible explanation for increased mortality during early life stages. Further, the results suggested an adaptive mechanism for establishing beneficial strains along the ontogenetic progression. Moreover, the highly transient microbiota in the early life stages became stable along the ontogenetic progression, hypothesizing that the earlier life stages will be the best window to influence the microbiota. The egg microbiota also crucially affected the microbial community. Noteworthily, both water and the feed microbiota significantly contributed to the early microbiota, with the feed microbiota having a more significant contribution to fish microbiota. The results illustrated that rotifer enrichment would be the optimal medium for the early larval microbiota manipulations. Briefly, the results highlighted the crucial foundations for the microbial ecology of T. blochii during early life stages with implications to develop suitable beneficial microbial management strategies for sustainable mariculture production.